2022
DOI: 10.1002/clc.23931
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific risk factors of carotid atherosclerosis progression in a high‐risk population of cardiovascular disease

Abstract: Background The progression of carotid intima‐media thickness (cIMT) and plaques are associated with cardiovascular health, especially for high‐risk population of cardiovascular disease (CVD). Hypothesis Risk factors for atherosclerosis may vary by sex. This study aimed to investigate the sex‐specific risk factors of cIMT and plaque progression. Methods We selected subjects who were identified as high‐risk population of CVD, and collected thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Moreover, the results showed that diabetes duration, TC, HbA1c, and HDL-C were also associated with CIMT thickening. However, the decision tree model excluded traditional factors such as smoking, sex, and hypertension, which may not be consistent with the results of most other studies [19,20] .There are several possible explanations: First, the de nition of high CIMT was different. In this study, a cut-off of 1.0 mm was used, which was more in line with the characteristics of the Chinese population; Second, the study population, sample size, study type, and inclusion and exclusion criteria were varied between studies.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, the results showed that diabetes duration, TC, HbA1c, and HDL-C were also associated with CIMT thickening. However, the decision tree model excluded traditional factors such as smoking, sex, and hypertension, which may not be consistent with the results of most other studies [19,20] .There are several possible explanations: First, the de nition of high CIMT was different. In this study, a cut-off of 1.0 mm was used, which was more in line with the characteristics of the Chinese population; Second, the study population, sample size, study type, and inclusion and exclusion criteria were varied between studies.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, smoking and drinking alcohol affected cIMT in adult women but not in men who presented higher cIMT values when diagnosed with hypertension [ 47 ]. The laboratory test results from the study initially suggested the potential importance of the presence of HLA-B27, but eventually no significant association was found.…”
Section: Discussionmentioning
confidence: 99%